Pengaruh Terapi Aktivitas Kelompok Art Painting terhadap Tingkat Sters pada Lansia di Panti Sosial Tresna Werdha Budi Mulia 2 Cengkareng - Tri Setyaningsih; Ribka Sabarina Panjaitan; Dameria Br Saragih; Fitri Adella; Desti Dwi Astuti (Jurnal Sains dan Kesehatan, 2026)
Stress in older adults needs attention because it can negatively affect physical, emotional, and social well-being, as well as overall quality of life. Elderly individuals living in social welfare institutions are particularly vulnerable to stress due to environmental changes, limited family involvement, loneliness, daily routines, and reduced independence. This study aimed to determine the effect of art painting group activity therapy on stress levels among older adults at Budi Mulia 2 Cengkareng Social Welfare Home. A quantitative pre-experimental study with a one-group pretest-posttest design was conducted involving 33 participants selected through total sampling. Stress levels were measured using the DASS-21 stress subscale. The intervention consisted of four art painting sessions lasting 30–45 minutes each. Data were analyzed using the Wilcoxon test. The mean stress score decreased from 22.18 before the intervention to 15.94 after the intervention. The Wilcoxon test showed a significant difference (p = 0.000), indicating that art painting group activity therapy effectively reduced stress levels among older adults.